Radiation Recall Pneumonitis on FDG PET/CT Triggered by COVID-19 Vaccination. (2nd March 2022) - Hughes, Nicola M.; Hammer, Mark M.; Awad, Mark M.; Jacene, Heather A.
Abstract: A 67-year-old man with metastatic lung adenocarcinoma was initially treated with whole-brain radiotherapy for intracranial metastases, followed by chemotherapy and pembrolizumab. After completing 2 years of systemic therapy, the primary right lung lesion was biopsy-proven to have residual adenocarcinoma, which was then treated with radiation (6000 cGy in 15 fractions). Follow-up serial FDG PET/CT showed radiation fibrosis. Eighteen months after radiotherapy, the patient received 2 doses of an mRNA COVID-19 vaccine. FDG PET/CT performed 4 days following his second vaccine dose showed FDG-avid multistation lymphadenopathy and radiation recall pneumonitis, likely vaccination-induced and mimicking recurrent disease. This resolved spontaneously without therapy.